Deciphering the uniqueness of Mucoromycotina cell walls by combining biochemical and phylogenomic approaches. (22nd September 2014) - Mélida, Hugo; Sain, Divya; Stajich, Jason E.; Bulone, Vincent
Summary: Most fungi from the Mucoromycotina lineage occur in ecosystems as saprobes, although some species are phytopathogens or may induce human mycosis. Mucoromycotina represent early diverging models that are most valuable for understanding fungal evolution. Here we reveal the uniqueness of the cell wall structure of the Mucoromycotina R hizopus oryzae and P hycomyces blakesleeanus compared with the better characterized cell wall of the ascomycete N eurospora crassa . We have analysed the corresponding polysaccharide biosynthetic and modifying pathways, and highlight their evolutionary features and higher complexity in terms of gene copy numbers compared with species from other lineages. This work uncovers the presence in Mucoromycotina of abundant fucose‐based polysaccharides similar to algal fucoidans. These unexpected polymers are associated with unusually low amounts of glucans and a higher proportion of chitin compared with N . crassa . The specific structural features are supported by the identification of genes potentially involved in the corresponding metabolic pathways. Phylogenomic analyses of genes encoding carbohydrate synthases, polysaccharide modifying enzymes and enzymes involved in nucleotide‐sugar formation provide evidence for duplication events during evolution of cell wall metabolism in fungi. Altogether, the data highlight the specificity of Mucoromycotina cell walls and pave the way for a finer understanding of their metabolism.